2016
DOI: 10.1002/anie.201510394
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the Electrocatalytic Turnover of Vitamin B12‐Mediated Dehalogenation on Single Soft Nanoparticles

Abstract: We report the electrocatalytic dehalogenation of trichloroethylene (TCE) by single soft nanoparticles in the form of Vitamin B12 -containing droplets. We quantify the turnover number of the catalytic reaction at the single soft nanoparticle level. The kinetic data shows that the binding of TCE with the electro-reduced vitamin in the Co(I) oxidation state is chemically reversible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
32
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 65 publications
2
32
0
Order By: Relevance
“…[32][33][34][35][36][37] Stochastic collision electrochemical measurements have been widely applied in many applications ranging from electrocatalytic amplification and direct electrochemical stripping of individual metal NPs to soft particles and blocking detection of biologically relevant samples. [38,39] Recently,Comptonsgroup assessed the electrocatalytic activity of single NPs by stochastic collision measurements. [40,41] This gave important and complementary insights into the conventional analysis usually performed on the ensemble measurements,o pening up anew possibility of testing the performance of nanomaterials in more realistic conditions when NPs are dispersed in the environment.…”
mentioning
confidence: 99%
“…[32][33][34][35][36][37] Stochastic collision electrochemical measurements have been widely applied in many applications ranging from electrocatalytic amplification and direct electrochemical stripping of individual metal NPs to soft particles and blocking detection of biologically relevant samples. [38,39] Recently,Comptonsgroup assessed the electrocatalytic activity of single NPs by stochastic collision measurements. [40,41] This gave important and complementary insights into the conventional analysis usually performed on the ensemble measurements,o pening up anew possibility of testing the performance of nanomaterials in more realistic conditions when NPs are dispersed in the environment.…”
mentioning
confidence: 99%
“…Simultaneous optical and electrochemical recordings provided comprehensive capability to correlate the physical movement of nanoparticles (from optical signal) and the electron transfer activity (from electrochemical signal). [16][17][18][19][20][21] Based on the different mechanisms, SNC studies can be classified into three typical categories: diffusion blockade, [22,23] electrocatalytic amplification, [24,25] and direct electrochemical oxidation. These results demonstrated that the electrical contact between nanoparticle and electrode, which could be rather stochastic due to thermal motion and micro-convection, played critical roles in regulating the multi-peak behavior of single silver nanoparticles.…”
mentioning
confidence: 99%
“…[10][11][12] This method has received widespread attention once proposed because it is simple, speedy, cost-effective and because it can detect the electrochemical response of a large number of individual NPs. [16][17][18][19][20][21] Based on the different mechanisms, SNC studies can be classified into three typical categories: diffusion blockade, [22,23] electrocatalytic amplification, [24,25] and direct electrochemical oxidation. In collision experiments, the frequency of collision, the magnitude and shape of the current response can provide rich information about NPs, including size distribution, concentration, and diffusion coefficient.…”
mentioning
confidence: 99%
“…The mechanism was revealed that the Co III in VB 12 was reduced into Co II and Co I through one or two electron transfer followed by the four‐electron reduction of oxygen . They also found that the binding of trichloroethylene with Co I in VB 12 was chemically reversible …”
Section: Development Of Nanoimpact Methodsmentioning
confidence: 99%
“…[32] They also found that the binding of trichloroethylene with Co I in VB 12 was chemically reversible. [33]…”
Section: C) Current Transients Of Particles Collision Onmentioning
confidence: 99%